The Effect of Scheduling Effectiveness and Work Fatigue on Cabin Crew Absenteeism and Its Impact on Performance Appraisal Outcomes at PT Garuda Indonesia - Ruth Fajarini; Wa Ode Zusnita Muizu (Amkop Management Accounting Review (AMAR), 2026)
The aviation industry requires high standards of safety and service quality, where cabin crew attendance is a fundamental operational requirement for commercial flights in accordance with CASR 121 Article 391. As a national full-service airline, PT Garuda Indonesia applies competency, discipline, and crew composition standards exceeding minimum regulatory requirements to maintain service quality and manage work fatigue. This study examines cabin crew absenteeism and its impact on performance appraisal outcomes and operational reliability. The study aims to identify factors influencing absenteeism, analyze the mediating role of work fatigue, and formulate strategies to optimize scheduling effectiveness and attendance. The research involved 106 active cabin crew members of PT Garuda Indonesia selected through purposive sampling. A mixed-method approach was employed, combining quantitative analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and qualitative analysis through open-ended questions. Primary data were collected through surveys, while secondary data were obtained from attendance records, work schedules, and performance appraisal results. The findings show that scheduling effectiveness has a negative and significant effect on absenteeism, work fatigue has a positive and significant effect on absenteeism, absenteeism negatively affects performance appraisal outcomes, and scheduling effectiveness and work fatigue indirectly influence performance appraisal outcomes through absenteeism.